The relationship between copper intake and chronic kidney disease/diabetic kidney disease: insights from NHANES data (2011-2018) - Hu, Shasha; Tian, Xiao; Wang, Zhenzhen; Li, Mengmeng (Frontiers in Endocrinology, 2025)
BackgroundThe connection between copper consumption and chronic kidney disease (CKD), as well as diabetic kidney disease (DKD), is still unclear. This research seeks to explore the link between copper intake and both CKD and DKD by analyzing data from the National Health and Nutrition Examination Survey (NHANES), which was carried out from 2011 to 2018.MethodsParticipant data were derived from the 2011–2018 NHANES database. For evaluating variable differences, complex sampling design - weighted t - tests were used for continuous variables, and weighted chi - square tests for categorical ones. Univariate regression analysis probed the relationship between variables and the dependent variable. Multivariate logistic regression analysis was employed to establish a multivariable model. Restricted Cubic Spline (RCS) curves were applied to explore the potential nonlinear association of copper intake with CKD and DKD.ResultsThe study involved 16,948 participants, comprising 3,319 individuals with CKD and 13,629 controls without CKD. The findings from the multivariate logistic regression analysis demonstrated negative correlation between copper intake and CKD (OR > 0.80) and DKD (OR > 0.5). This protective effect was observed consistently across all analyzed population subgroups. Furthermore, the RCS analysis suggested a possible non-linear association between copper intake and CKD and DKD. An inverse association was observed between copper intake and CKD in the group with copper intake ≤ 1.47 mg (OR = 0.51), and between copper intake and DKD in the group with intake ≤ 0.98 mg (OR = 0.40).ConclusionCopper intake was found to be significantly negatively associated with CKD and DKD within a certain range.